Case report: Pulse cyclophosphamide for treatment of multi-agent-refractory hepatic graft-versus-host disease - Cai, Yijun; Ali, Amir; Filler, Elan; Bayati, Rua; Toma, Tanjia; Zaki, Omar; Yaghmour, George; Ladha, Abdullah; Woan, Karrune; Tam, Eric; Chaudhary, Preet M. (Frontiers in Oncology, 2024)
Graft-versus-host disease (GVHD) is a common complication in patients receiving allogeneic hematopoietic stem cell transplantation (HSCT). GVHD is characterized as either acute or chronic based on symptomatology and histopathological findings. Despite advancements in disease-targeting therapeutics, steroid-refractory GVHD remains a significant contributor to mortality in HSCT recipients, highlighting the gaps in our understanding of its pathophysiology and treatment strategies.We present the case of a 46-year-old female diagnosed with acute undifferentiated leukemia, who exhibited persistently elevated levels of serum total bilirubin (T.Bili), alkaline phosphatase (ALP), and liver function tests (LFTs) beginning on [Day +201] post-haploidentical peripheral blood stem cell (PBSC) transplantation. The patient received fludarabine/total body irradiation (Flu/TBI) as a myeloablative conditioning regimen and post-transplant cyclophosphamide/tacrolimus/mycophenolate mofetil (PTCy/Tac/MMF) as GVHD prophylaxis. A liver biopsy confirmed the diagnosis of GVHD, while other possible etiologies were excluded by corresponding tests. Initial treatment with prednisone and tacrolimus, as well as the later addition of ruxolitinib, all showed poor response indicated by worsening T.Bili, ALP, and LFTs at the same time. Based on a multidisciplinary comprehensive assessment, we decided to administer 1000 mg/m 2 (1600 mg) of cyclophosphamide ("pulse Cy"), which resulted in a dramatic improvement in T.Bili and transaminases starting from the very next day. A durable response to pulse cyclophosphamide was observed as all indicators normalized ("complete response") within 55 days without relapses. The patient remains in good health with no recurrence of hepatic GVHD.To our knowledge, this is the first case in which Grade IV hepatic GVHD, refractory to multiple agents including steroids, tacrolimus, and ruxolitinib, demonstrated a complete response to pulse cyclophosphamide. The success highlights the potential therapeutic role of cyclophosphamide, a potent and cost-effective chemotherapy agent, in treating multi-agent-refractory GVHD. Large-scale clinical trials are warranted to validate its efficacy in this setting.